2018
DOI: 10.1111/rssa.12436
|View full text |Cite
|
Sign up to set email alerts
|

A Bayesian Semiparametric Approach for Trend–Seasonal Interaction: an Application to Migration Forecasts

Abstract: Summary We model complex trend–seasonal interactions within a Bayesian framework. The contribution divides into two parts. First, it proves, via a set of simulations, that a semiparametric specification of the interplay between the seasonal cycle and the global time trend outperforms parametric and non‐parametric alternatives when the seasonal behaviour is represented by Fourier series of order bigger than 1. Second, the paper uses a Bayesian framework to forecast Swiss immigration, merging the simulations’ ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…After a series of rearrangements, it can be shown that a penalized likelihood can be used to estimate ( , ) δ θ i j . For all the mathematical details in a frequentist and in a Bayesian framework see (Milivinti and Benini, 2018). The precision of the approximation is function of the total amount of points.…”
Section: Despite Being Elegant and Concise The Previous Equation Igno...mentioning
confidence: 99%
“…After a series of rearrangements, it can be shown that a penalized likelihood can be used to estimate ( , ) δ θ i j . For all the mathematical details in a frequentist and in a Bayesian framework see (Milivinti and Benini, 2018). The precision of the approximation is function of the total amount of points.…”
Section: Despite Being Elegant and Concise The Previous Equation Igno...mentioning
confidence: 99%